First measurement of Γ(D(s)(+) → μ+ν) / Γ(D(s)(+) → φ π+) - Acosta, D. (Institutional Knowledge at Singapore Management University, 1994)
We present a measurement of Γ(D+s→μ+ν) / (D+s→φπ+)=0.245±0.052±0.074. Using this ratio and B(D+s→φπ+)=(3.7±0.9)% we extract fDs=344±37±52±42 MeV, where the last error is due to the uncertainty in the D+s→φπ+ absolute branching ratio. This result is larger than most theoretical predictions.